Relationship between humidity and physiology in warm and humid conditions: A literature review - DZYUBAN, Yuliya (Institutional Knowledge at Singapore Management University, 2020)
Change in precipitation patterns caused by global warming will likely increase humidity in some areas of the world. Moreover, populations in tropical climates with already high humidity levels can experience an added stress on their health and thermal comfort due to an amplifying effect of heat and moisture. Humidity is a generic term commonly used to describe moisture in the air. However, there are numerous variables that describe different properties of humid air that can be used in scientific studies. While relative humidity remains the most used, it has several shortcomings associated with its high correlation with air temperature. Thus, it is important to understand the differences between the variables that describe atmospheric moisture and their proper applications in scientific studies. Furthermore, to maintain outdoor thermal comfort in warm and humid world, the effect of atmospheric moisture on human physiology must be explored. This report will first provide definitions and descriptions of the main atmospheric moisture variables and their proper application. Then, it will explain the human heat balance and how it is achieved through physiological body systems, and provide the overview of scientific studies to date exploring how warm and humid conditions affect human physiology and heat perceptions depending on the activity levels and demographic characteristics. Lastly, it will provide the summary of findings and identify the pathways for future research